Analisis Prinsip Program Assalam Arabic Course (AAC) Berdasarkan Total Quality Management (TQM) Di Pondok KMI Assalam Bangilan Tuban - Maulidiyah, Robiatul Laili; Taufiqurrahman; Hasaniyah, Nur (Shaut al Arabiyyah, 2024)
The purpose of this study was to determine the management of the institution, especially the Assalam Arabic Course (AAC) program based on the Principle of Total Quality Management. The research method used is a descriptive qualitative research type. While the results of this study are: 1) the focus of the AAC program users are students of the KMI Assalam Islamic Boarding School, 2) Leadership in the AAC program is led by the AAC Supervisor and below him there is a Responsible Person (Head of the AAC Program), 3) Involvement of human resources involving all aspects of the institution including teachers, students, and principals including parents, 4) The AAC Program approach is one approach to achieving the mission of the Islamic Boarding School, 5) Decisions based on evidence of the AAC Program based on evaluation and existing curriculum, and 6) Management relationships that adopt books from the Darussalam Gontor Islamic Boarding School and also the Institute of Islamic and Arabic Language Sciences (LIPIA).